Spatiotemporal Land Cover Change and Future Hydrological Impacts Under Climate Scenarios in the Amazonian Andes: A Case Study of the Utcubamba River Basin - Abner S. Rivera-Fernandez; Alexander Cotrina-Sanchez; Rolando Salas López; Jhon A. Zabaleta-Santisteban; Ney Rios; Angel J. Medina-Medina; Katerin M. Tuesta-Trauco; José A. Sánchez-Vega; Teodoro B. Silva-Melendez; Manuel Oliva-Cruz; Cecibel Portocarrero; Elgar Barboza (Land, 2025)
Understanding how land use and climate change jointly affect water availability is essential for sustainable planning in tropical Andean–Amazonian basins. This study focuses on the Utcubamba River Basin in northeastern Peru, a data-scarce and socioecologically strategic watershed where land transformation and climate variability converge. A multi-temporal land use/land cover (LULC) analysis (1990–2024) was conducted, coupled with hydrological modeling using the SWAT model under historical and future climate scenarios (SSP2–4.5 and SSP5–8.5), including the spatial overlay of the LULC change concentration with key hydrological indicators. LULC classifications revealed forest loss and the expansion of pasture, agriculture, and shrubland areas, particularly in the upper basin. Hydrological projections showed significant changes in water flow, including reductions in minimum monthly flows by up to 73.9% and increases in peak flows by 14.8% under the SSP5–8.5 scenario. The water balance is expected to shift, with increased percolation and reduced lateral flow, suggesting decreased storage capacity. By identifying critical sub-basins where land degradation and water insecurity converge, the study supports adaptive strategies for land restoration, aquifer recharge planning, and ecosystem conservation. Despite limited hydrological infrastructure, the SWAT model effectively simulated water dynamics, aiding climate resilience and water security efforts in the Amazonian Andes.